Validity Evidence of the Brazilian Version of Characteristics of Resilience in Sports Teams Inventory - Mylena Aparecida Rodrigues Baransk; José Roberto Andrade do Nascimento Junior; Mauro Moreira dos Santos; Gabriel Lucas Morais Freire; Lorcan Donal Cronin; Daniel Perez Arthur; Joice Mara Facco Stefanello (Journal of Clinical Sport Psychology, 2025)
This multistudy research aimed to adapt and validate the Characteristics of Resilience in Sports Teams Inventory for the Brazilian sports context. The study involved four translators, 25 athletes in the pilot study, five experts, and 1,155 athletes (581 females and 574 males) from team sports, such as basketball, soccer, futsal, American football, handball, volleyball, and beach soccer. In Study 1, all Characteristics of Resilience in Sports Teams Inventory for the Brazilian sports context items achieved coefficient of content validity total above the cutoff (0.80), with the entire questionnaire reaching a corrected content validity coefficients total of 0.99. Study 2 confirmed the instrument’s two characteristic dimensions, its factorial structure, and internal consistency (comparative fit index = .92; Tucker–Lewis’s index = .90; standardized root mean squared residual = .04). Study 3 found that the resilience scale had positive correlations with team cohesion and collective efficacy, while the vulnerability under pressure dimension showed negative correlations. The study concludes that the 20-item Characteristics of Resilience in Sports Teams Inventory for the Brazilian sports context can effectively assess team resilience in the Brazilian sports context.